COMPOSITION, ANTIBACTERIAL AND ANTIOXIDANT ACTIVITIES OF ARTEMISIA HERBA-ALBA ESSENTIAL OILS FROM ALGERIA - Hamzaoui, N. Dahmani-; N., Sabaou3; S., Salido (university of el oued/جامعة الوادي, 2017)
The essential oils of three individual plants of Artemisia herba-alba, growing wild in tree different locations from Bordj Bou Arrérridj in East Algeria has been extracted by hydrodistillation and a microwave distillation process. The main components were α-thujone (35.1 and 31.2% in HD and MD oils, respectively) for Draâ Ech, davanone (39.6-37.3%) and 1, 8-cineole (9.2-7.8%) for Bordj Ghédir, chrysanthenone (29.6-43.8%), camphor (18.6-16.0%), and α-thujone (15.9-8.6%) for Bordj Bou Arrérridj. In comparison with HD, MD allows to obtain oil in a very short time, with the comparable qualities and substantial saving of energy. The minimum inhibitory concentration of various essential oils shows a power inhibitor not exceeding 10 µg/mL against all microbial strains. The three chemotypes were slightly active, and the weak DPPH radical scavenging activity of these oils could be attributed to the absence of some phenolic components.
Articel
Keywords: Artemisia herba-alba, essential oils, microwave distillation, antibacterial activity, antioxidant activity